A Novel Model of Emergency Demand Response Program for Optimal Aggregators' Strategy. Issue 1 (20th January 2022) - Hosseini, Seyyed Ebrahim; Najafi, Mojtaba; Akhavein, Ali
Abstract: Demand response (DR) programs have been used for a variety of purposes. In this study, Emergency Demand Response Program (EDRP), as an incentive-based program, is used for peak clipping, managing the volatility and the increase of the electricity prices, monetizing consumers' involuntary electricity outage and controlling the price in the day-ahead market. A market-driven model in the form of a combination of Diamond's over-lapping generations (OLG) and Price Elasticity (PE) formulations is proposed for the aggregates (AGGs) by which they can manage their consumers' demand at the peak hours and maximize the profit. Furthermore, maximizing the profit of the AGGs was performed by determining the optimal amount of demand while three technical constraints such as demand ceiling, relative risk aversion and incentive limits were also included in the proposed model. The profit function of the AGGs is considered in the form of the difference between the revenue and the cost. The problem is solved with taking into consideration the different rate of time preference and PE over a 24-hour period. The simulation results showed a successful performance of the proposed model from the considered economical and technical viewpoints.